1994
DOI: 10.1126/science.8197455
|View full text |Cite
|
Sign up to set email alerts
|

Jak-STAT Pathways and Transcriptional Activation in Response to IFNs and Other Extracellular Signaling Proteins

Abstract: Through the study of transcriptional activation in response to interferon alpha (IFN-alpha) and interferon gamma (IFN-gamma), a previously unrecognized direct signal transduction pathway to the nucleus has been uncovered: IFN-receptor interaction at the cell surface leads to the activation of kinases of the Jak family that then phosphorylate substrate proteins called STATs (signal transducers and activators of transcription). The phosphorylated STAT proteins move to the nucleus, bind specific DNA elements, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
3,797
5
61

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 5,511 publications
(3,915 citation statements)
references
References 69 publications
52
3,797
5
61
Order By: Relevance
“…Levels of STAT3 bound to the miR‐7 promoter probe, observed in E2‐treated young fibroblasts, may be causative of increased EGFR expression and activity, as recent research has identified an increase in STAT3 signaling in the presence of EGFR/IL6R association and co‐activation (Wang et al ., 2013). STAT1 forms complexes with STAT2 and IRF9 to activate ISGF3G/ISRE (Darnell et al ., 1994); however, STAT3 suppressed STAT1‐dependent gene activation and inhibited STAT1 heterodimer formation (Ho & Ivashkiv, 2006). Furthermore, in tumor cell lines, STAT3 promoted proliferation and cell survival, while STAT1 was antiproliferative and pro‐apoptotic (Pensa et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of STAT3 bound to the miR‐7 promoter probe, observed in E2‐treated young fibroblasts, may be causative of increased EGFR expression and activity, as recent research has identified an increase in STAT3 signaling in the presence of EGFR/IL6R association and co‐activation (Wang et al ., 2013). STAT1 forms complexes with STAT2 and IRF9 to activate ISGF3G/ISRE (Darnell et al ., 1994); however, STAT3 suppressed STAT1‐dependent gene activation and inhibited STAT1 heterodimer formation (Ho & Ivashkiv, 2006). Furthermore, in tumor cell lines, STAT3 promoted proliferation and cell survival, while STAT1 was antiproliferative and pro‐apoptotic (Pensa et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…GAF/AAF is formed by homodimerization of the tyrosine phosphorylated Stat1, and ISGF3 is a heterotrimermic complex consisting of the phosphorylated Stat1 and Stat2, and the major DNA binding component p48. In contrast to these two factors, the activation of which does not require de novo protein synthesis, induction of IRF-1 activity by IFNs is controlled by GAF/AAF, whose binding site is found in the IRF-1 promoter (reviewed in Darnell et al 1994;Bluyssen et al 1996;Taniguchi et al 1997). Recent studies using IRF-1, p48 or Stat1 deficient mice revealed that these transcription factors are all critical for the antiviral response to IFNs (Kimura et al 1994;Reis et al 1994;Durbin et al 1996;Kimura et al 1996;Meraz et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Although not previously linked to chemokine receptor-ligand signaling, expression of several of these genes such as interferon-induced transmembrane protein 2 (IFITM2) and growth hormone inducible transmembrane protein (GHITM) are recognized to be a part of the interferon signaling system that includes Janus kinases and their downstream target STAT proteins [39,40]. IFITM2 is a member of the large 1–8 gene family whose members are strongly induced by both type I (IFNα, IFNβ) and type II (IFNγ) interferons [41,42].…”
Section: Discussionmentioning
confidence: 99%